Organizational Culture Transformation and Public Service Effectiveness: Evidence from the Investment and One-Stop Integrated Service Office of Riau Islands Province - Munarmi Munarmi; Rudi Subiyakto; Dedi Afrizal (International Journal of Social Sciences and Humanities, 2026)
Work culture is a strategic element in determining the effectiveness of public service delivery. The Investment and One-Stop Integrated Service Office of Riau Islands Province has experienced organizational transformation through the simplification of bureaucratic structures, digitalization of licensing services, and implementation of the Core Values of BerAKHLAK for civil servants. However, several challenges remain, including unequal digital competencies among employees, adaptation to functional positions, and consistency in implementing performance management systems. This study aims to analyze the work culture within the organization using Denison's Organizational Culture Theory. A qualitative descriptive approach was employed through interviews, observations, and document analysis. The findings indicate that employee involvement has improved through functional positions, although competency development remains uneven. Organizational consistency is supported by the implementation of BerAKHLAK values, yet coordination among units still requires strengthening. Adaptability has increased through digital service transformation, but technological mastery remains a challenge for some employees. The mission dimension demonstrates that employees generally understand organizational objectives related to investment and licensing services. The study concludes that the organizational work culture is progressing toward a more adaptive, professional, and service-oriented culture, although continuous efforts are needed to strengthen collaboration, digital competencies, and organizational integration.